A micro-force measurement system based on high-temperature superconducting magnetic levitation. (30th September 2019) - Yang, Wenjiang; Ji, Yu; Ye, Mao; Tang, Haibin
Abstract: A thrust stand based on high-temperature superconducting (HTS) magnetic levitation technology capable of measuring the micro-thrust in two methods is presented in this paper. The stand mainly consists of a superconducting array, a permanent magnetic levitation platform, refrigerating devices, optical measuring devices, calibration devices and a data acquisition system. HTS magnetic levitation technology was used to provide a platform for micro-force measurements due to its low-friction and high-load-bearing characteristics. The measurements are divided into a direct method and an indirect method according to the principles. The direct method is required to measure the angular displacement of the platform and convert it into thrust with proper calibration. The indirect method, on the other hand, is required to measure the angular velocity to calculate the thrust according to the angular momentum theorem. Experiments indicate that, although the hysteresis loss of the HTS levitation system is unavoidable and may affect the accuracy of the system, it can be reduced effectively by multiple calibrations. The calibration results illustrate excellent repeatability and linearity. A propeller thruster is used to verify the performance of the stand. Four sets of micro-force with different propeller speeds were tested. The relative error between results from both methods at each speed was 11.48%, 18.11%, 22.73% and 21.00%. The direct method is more accurate and has fewer sources of uncertainty. It presents a new approach for measuring micro-thrust.